Characterization of particle sources and comparison of different particle metrics in an urban detached housing area, Finland. (1st March 2022) - Teinilä, K.; Timonen, H.; Aurela, M.; Kuula, J.; Rönkkö, T.; Hellèn, H.; Loukkola, K.; Kousa, A.; Niemi, J.V.; Saarikoski, S.
Abstract: Particulate matter (PM) is emitted from various anthropogenic sources in urban areas affecting the local air quality. The aim of this study was to characterize the sources influencing air quality in detached house area in the Helsinki metropolitan area in Finland, and secondly, to explore the additional value of new particle physical properties to assess the impact of residential combustion on air quality. Measurements were conducted in an urban detached housing area between January and April 2019. Measured particle physical properties were particle number (PN), particle mass (PM1 ) and lung deposited surface area (LDSA) concentrations and number size distributions. In addition, particle chemical composition was measured using a soot particle aerosol mass spectrometer (SP-AMS; organic compounds, inorganic ions) and an aethalometer (black carbon (BC)). Concentrations of selected monosaccharide anhydrides and polycyclic aromatic hydrocarbons were analysed from the PM10 filter samples. The sources and characteristics of organic aerosol was investigated by applying positive matrix factorization to the mass spectra measured with the SP-AMS. Based on the variations in the measured particle physical parameters, chemical species and meteorology, the measurement period was divided into three sub periods dominated by urban background, wood burning and long-range transport (LRT) aerosols. Highest pollutant concentrations were measured during the wood burning and LRT periods. Wood burning increased the concentrations of all measured species, but the differences were most significant to levoglucosan, benzo(a)pyrene, BC and PM1 that had 12, 10, 6.4 and 3.6 times larger mean concentrations during the wood burning period compared to the urban background period, respectively. LRT affected significantly levoglucosan, PM1 and BC concentrations, since LRT pollutants partly originated from open biomass fires in Eastern Europe. The impact of local wood burning and LRT was quite small to particle number concentrations, whereas LDSA concentrations and size distributions were affected by traffic, wood combustion emissions and LRT. BC concentration correlated with the LDSA concentration during all periods suggesting a common origin. Particle number concentration was a good indicator of local combustion, especially traffic emissions, while the PM1 mass concentration together with secondary particle material was a good measure for the LRT pollutants. Benzo(a)pyrene was found to be a good indicator of local wood burning, but it was not detected in LRT biomass combustion particles. Highlights: The sources influencing air quality in detached house area in the Helsinki metropolitan area were characterized. Special attention was paid on the parameters that can be utilized to estimate the main particle sources and to assess their impact on air quality. Elevated PM1 concentration was attributed especially to the LRT and local wood burning in fireplaces.